Pengaruh Karakteristik Auditor Dan Karakteristik Perusahaan Terhadap Audit Report Lag - Susanto, Androni; Utama, Audyla Fitria (Universitas Gorontalo, 2022)
This study aims to analyze two characteristics, namely the characteristics of the auditor which consist of, 1) The influence of the auditor's reputation on the Audit Report Lag, and 2) The effect of the auditor's tenure on the Audit Report Lag. The second characteristic is the company's characteristics which consist of, 1) The effect of the effectiveness of the audit committee on the Audit Report Lag, 2) The effect of accounting complexity on the Audit Report Lag, 3) The effect of the company's financial condition on the Audit Report Lag, 4) The influence of profitability on the Audit Report Lag. This study obtained data samples from financial reports and annual reports from 2017 to 2021 of entities listed on IPOs on the Indonesia Stock Exchange (IDX) from 2017. This study uses multiple linear regression analysis techniques with the help of SPSS software version 25. From the results of the study, it can be partially concluded that only the accounting complexity variable has no significant effect on the delay in audit reports.